Предмет: Алгебра,
автор: nikitintima46
Решить систему уравнений:
Приложения:
Ответы
Автор ответа:
0
{x^2+y^2=13;
{xy=-6
x = -6 / y
( -6 / y ) ^2 + y^2 = 13
36/y^2 + y^2 = 13
36 + y^4 = 13y^2
y^4 - 13y^2 +36 = 0
y^2 = t
t^2 - 13t +36=0
по теореме виета
t1+t2=13
t1*t2=36
t1= 4 t2= 9
вернемся к y
y^2=4 y=2; -2
y^2=9 y=3 ;-3
x=-6/2 x=-3; 3
x= 6/3 x =-2 ;2
{xy=-6
x = -6 / y
( -6 / y ) ^2 + y^2 = 13
36/y^2 + y^2 = 13
36 + y^4 = 13y^2
y^4 - 13y^2 +36 = 0
y^2 = t
t^2 - 13t +36=0
по теореме виета
t1+t2=13
t1*t2=36
t1= 4 t2= 9
вернемся к y
y^2=4 y=2; -2
y^2=9 y=3 ;-3
x=-6/2 x=-3; 3
x= 6/3 x =-2 ;2
Автор ответа:
0
легче решать сложением
Приложения:
Похожие вопросы
Предмет: Математика,
автор: bambansdana22
Предмет: Геометрия,
автор: polina071207
Предмет: Биология,
автор: anna2983
Предмет: Физика,
автор: Аноним
Предмет: Алгебра,
автор: Herf